Investigation of microscopic mechanisms for water-ice phase change propagation control. (March 2022) - Weng, Yu-Kai; Shin, Seungha; Kihm, Kenneth D.; Bahzad, Mohammad; Aaron, Douglas S.
Highlights: Ice growth speed is determined by atomic mobility and thermodynamic driving force. A lower surface energy of ice crystal leads to a slower ice propagation. Surface interaction rearranges ice crystal or graphene flakes during freezing. Due to the rearrangement, ice grows faster in parallel to the graphene surface. Abstract: The influence of thermodynamic and structural conditions on water-ice phase change process was investigated with consideration of graphene-water surface interactions for fundamental understanding and effective control of freezing propagation. The phase change propagation as well as structural and energetic properties during the phase change were examined by analyzing atomic data from molecular dynamics simulations. The freezing propagation speed is affected by the competition between atomic mobility and thermodynamic driving force for phase change, which causes an optimal temperature for fast ice growth to appear at 252 K. In addition, the water-ice interfacial energy, which depends on the orientation of the water-contacting ice surface, changes interfacial structural stability and thus freezing propagation, i.e., a higher interfacial energy leads to a faster ice propagation. Therefore, we suggest that the water-ice phase change propagation can be controlled by adjusting the orientation of ice crystal. The surface interactions, or graphene-water interactions in this research, affect the energetics near the water-surface interface. The energetic change rearranges the ice crystal or surface structures to reach the most stable ice-surface configuration or minimum energy state, in which the basal plane of the ice crystal is parallel with the graphene surface. As ice propagation is the slowest perpendicular to the basal plane, ice can grow faster parallel to graphene surface. The findings from this study provides insights to ice propagation control mechanisms for versatile freeze casting and its broader applications.